If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 58 = (a) + 2(b) + (c) 58 = a + 2(b) + (c) 58 = a + 2b + c Solving 58 = a + 2b + c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 58 + -1a = a + 2b + -1a + c Reorder the terms: 58 + -1a = a + -1a + 2b + c Combine like terms: a + -1a = 0 58 + -1a = 0 + 2b + c 58 + -1a = 2b + c Add '-58' to each side of the equation. 58 + -58 + -1a = 2b + -58 + c Combine like terms: 58 + -58 = 0 0 + -1a = 2b + -58 + c -1a = 2b + -58 + c Reorder the terms: -1a = -58 + 2b + c Divide each side by '-1'. a = 58 + -2b + -1c Simplifying a = 58 + -2b + -1c
| F(x)=40-.15x | | -6(2-9b)=17 | | q=20+47 | | 25+10w+w^2=0 | | -84=2(-6n-6) | | 24x=480 | | X^2-4x-8=-x+20 | | 3x/5-1x/10=1x/2+1 | | 1000-n=857 | | 4x^2+8x+4=1 | | x^4-6x^3+11x^2-18=0 | | 4.7-(0.3+q)=-10(1.1q-(0.1-q)) | | m-7=43 | | -8+4+3n=23 | | 19+3x=-2+8x | | -2(8v-2)+4v=6(v+2) | | y-2x+(3-z)= | | 164=6(a)+4(b)+4(c) | | 2x^2+x^2-8x-4=0 | | 6.1x+1=5.1x | | 4v-24=9(v-6) | | 32-X=25 | | 10u-7u=21 | | 1+8x=-16+31 | | Y=6x+12+2cosx | | 6y=4x+22 | | 5x^2+5y^2+4y+2=0 | | 4x^2+90x-500=0 | | 2(2k+5)-9k+8+3= | | n(5)=-1-5+4 | | 5x+8x-80=60-7x | | 3(x+4)+1=22 |